Analysis of Employee Loyalty with Job Satisfaction as Intervening Variable - Erika Dwi Athala; Efriyani Sumastuti (PT. PENERBIT TIGA MUTIARA, 2024)
The objective of this study is to examine the influence of factors such as work motivation, salary, work environment, and career development on employee loyalty. It also explores the role of employee job satisfaction as a mediator in this relationship. The research will be conducted at 9 coffee shops located in Semarang City. The population involved in this study consists of all employees working at 9 coffee shops in Semarang City. The sample used comprises 98 individuals who have been working for more than 1 year. Data analysis in this study was conducted using the SmartPLS 3.0 software. Testing hypotheses using the PLS method. The findings indicated that the job satisfaction of coffee shop workers in Semarang City was impacted by factors such as motivation, salary, work environment, and career growth. Enhanced work drive and remuneration will lead to heightened job contentment. Similarly, an improved work environment and opportunities for professional growth would enhance employee job satisfaction. One thing that affects loyalty is job satisfaction. This suggests that when job satisfaction grows, employee loyalty also increases. Job satisfaction acts as a mediator between salary and loyalty, work environment and loyalty, and career development and loyalty. However, it does not act as an intermediary between work motivation and loyalty.